Screen printed digital circuits based on vertical organic electrochemical transistors. (3rd November 2017) - Andersson Ersman, Peter; Westerberg, David; Tu, Deyu; Nilsson, Marie; Åhlin, Jessica; Eveborn, Annelie; Lagerlöf, Axel; Nilsson, David; Sandberg, Mats; Norberg, Petronella; Berggren, Magnus; Forchheimer, Robert; et al.
Abstract: Vertical organic electrochemical transistors (OECTs) have been manufactured solely using screen printing. The OECTs are based on PEDOT:PSS (poly(3, 4-ethylenedioxythiophene) doped with poly(styrene sulfonic acid)), which defines the active material for both the transistor channel and the gate electrode. The resulting vertical OECT devices and circuits exhibit low-voltage operation, relatively fast switching, small footprint and high manufacturing yield; the last three parameters are explained by the reliance of the transistor configuration on a robust structure in which the electrolyte vertically bridges the bottom channel and the top gate electrode. Two different architectures of the vertical OECT have been manufactured, characterized and evaluated in parallel throughout this report. In addition to the experimental work, SPICE models enabling simulations of standalone OECTs and OECT-based circuits have been developed. Our findings may pave the way for fully integrated, low-voltage operating and printed signal processing systems integrated with e.g. printed batteries, solar cells, sensors and communication interfaces. Such technology can then serve a low-cost base technology for the internet of things, smart packaging and home diagnostics applications.